Studi Tentang Model Pembelajaran Matematika Efektif Pada Anak Berkebutuhan Khusus di SLB - Saimun Saimun (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to analyze effective mathematical learning models in children with special needs in Special Schools. The researcher used a questionnaire in the data collection process. The respondents consisted of teachers, students, principals and academics in the Special School. The results of the study show that children with special needs at the Special School especially for mentally retarded children use thematic learning models. Thematic learning models contribute significantly to the learning process in Special Schools in order to create effective learning especially in mathematics because they have achieved effective learning indicators.